2021
DOI: 10.1155/2021/1347342
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Moxibustion for Breast Cancer Patients with Chemotherapy-Induced Myelosuppression during Adjuvant Chemotherapy: A Randomized Controlled Study

Abstract: Objective. The randomized controlled clinical trial aims to investigate the clinical efficacy of moxibustion for breast cancer patients with chemotherapy-induced myelosuppression (CIM) during adjuvant chemotherapy. Methods. Surgically resected breast cancer patients were randomly divided into the moxibustion group (MOX; n = 48) and control group (CON; n = 44). Routine adjuvant chemotherapy (every 21 days, 4–8 cycles) and supportive recombinant human granulocyte colony-stimulating factor were given to both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…In total, there were 51 studies remaining for full manuscript review, of which 41 studies were excluded due to the following reasons: different target population (n = 17), study protocols (n = 2), non-relevant outcomes (n = 21), non-RCT study design (n = 1). Finally, ten studies 29-38 were included for further qualitative and quantitative analyses. The PRISMA flow diagram of the review process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, there were 51 studies remaining for full manuscript review, of which 41 studies were excluded due to the following reasons: different target population (n = 17), study protocols (n = 2), non-relevant outcomes (n = 21), non-RCT study design (n = 1). Finally, ten studies 29-38 were included for further qualitative and quantitative analyses. The PRISMA flow diagram of the review process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [31][32][33] reported neither the procedure for allocation concealment nor blinding of participants and personnel in the research, so they presented a high risk of bias. For the item of blinding of the outcome assessment, four 29,33,36,38 were classified as having low risk, and one had high risk. In terms of how the studies addressed incomplete outcome data, 8 studies [29][30][31][32][33][34][35]38 were classified as having low risk with reported rates of follow-up and withdrawal, and the remaining 2 had high risk.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations